Moral Development of the Main Character in The Husky and White Cat Shizun - Cinta Violeta; I Made Rajeg; Ni Made Ayu Widiastuti (Jurnal Pendidikan dan Sastra Inggris, 2025)
This article investigated the moral development of the main character in the novel The Husky and His White Cat Shizun. The research aimed to identify the main character's moral development stages and examine how the main character’s personality relates to these stages throughout the story. This study focused on understanding the stages of the main character's moral reasoning development within the context of the novel. To achieve the research's aims, the study utilized data from the novel, employing documentation and observation methods along with a note-taking technique for data collection. Through this approach, the study explored the moral development of the main character, Mo Ran. The key findings of this research reveal that Mo Ran undergoes six stages of moral development. The analysis demonstrates that Mo Ran’s moral reasoning develops into a more complex and principled understanding of morality. The findings indicate Mo Ran’s character develops his moral understanding, moving from self-centeredness to a more complex principled sense of morality.